Pemberdayaan Ibu Rumah Tangga melalui Literasi Keuangan untuk Mewujudkan Kesejahteraan Ekonomi Keluarga - Utami, Dwi; Dewi, Desi Ratna; Salma, Dini Kamilia; Hastharita, Rafiqa; Arisah, Nur (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
This Community Service Program (PKM) aims to enhance the financial literacy of housewives through an understanding of household budgeting in order to achieve family economic welfare. The program was conducted in Tamallayang Village, Bontonompo District, involving 20 participants. The method used was interactive education through socialization and open discussions, with evaluation conducted using pre-test and post-test instruments. The results showed a significant improvement in participants' understanding of various aspects of financial literacy. This was indicated by increased scores across all measured indicators, including understanding of budgeting concepts, the ability to distinguish between needs and wants, and long-term financial planning. In addition, the program also improved participants’ awareness and attitudes toward managing household finances in a more planned and responsible manner. Therefore, the financial literacy program proved to be effective in enhancing the capacity of housewives in financial management, which ultimately contributes to improving family economic welfare.